PENGALAMAN KARIES, KADAR HAEMOGLOBIN, BERAT BADAN DAN TINGGI BADAN PADA ANAK DENGAN LESI MUKOSA ORAL - Indah Suasani Wahyuni; Fajar Fatriadi; Diani Prisinda; Fidya Meditia Putri; Nanan Nuraeny; Wahyu Hidayat (Faculty of Dentistry, Universitas Islam Sultan Agung, 2017)
Background: Oral mucosal lesions in children caused by nutritional problems, dental infection, poor oral hygiene and trauma. Oral health in children as the next generation of the nation should always be maintained. However there is still lack of data on the emergence of oral mucosal lesions in Indonesian children. Purpose. To describe an overview of the caries experience, Haemoglobin/Hematokrit (Hb Ht), weight (BB) and height (TB) in children aged 6-7 years in several elementary schools at Tanjungsari, Sumedang.Result: 44 of 137 students who had oral mucosal lesions, had completesupporting data. Total of 43 students had an average caries experience of 8.4 teeth/child (1-17 teeth/child), while 1 student was caries-free. The average of weight = 19.3 kg, height = 115.5 cm, and Hb/Ht = 12.5/36.5%. Oral lesions found were plaques on the tongue, ulcers, macules, nodules, pustules and desquamatives.Discussion: The condition of untreated dental caries can cause pain anddiscomfort, so the child will have difculty eating and interfere with the growth process. This can be seen through the child’s caries experience with data on weight and height. Tooth decay aﬀects the nutrient intake and was estimated to lead to a decrease in Hb/Ht. Oral mucosal lesions due to trauma and poor oral hygiene were not expected to aﬀect systemic conditions.Conclusion: The results of this study indicate that the caries experience was very high, the average value of weight and height were normal below the ideal, Hb/Ht levels within normal limits, while Coated tongue was the common diagnosis found from subjects